Pemberdayaan Kelompok Tani Desa Tongkok Untuk Meningkatkan Keterampilan Melalui Produksi Bioetanol Dari Ampas Kopi - lovisia, endang; Syabawaihi, Syabawaihi; Lestari, Fitri (Jurnal Mandala Pengabdian Masyarakat, 2025)
This community service activity aims to improve the skills of 18 members of the farmers’ group in Tongkok Village, Lahat Regency, in utilizing coffee husk waste as a raw material for renewable energy in the form of bioethanol. The implementation methods include socialization, technical training, and evaluation through pre-test and post-test questionnaires to measure participants’ skill improvement. From 70 kg of dried coffee husk waste, the fermentation process and three-stage distillation produced approximately 5 liters of bioethanol with an ethanol content of around 70%, which has the potential to be used as an alternative household-scale energy source. The skill evaluation results show that 83% of the participants are in the high category based on the skill interpretation table, indicating that they have successfully mastered the skills required for bioethanol production. Thus, this activity has effectively improved the community’s ability to process coffee husk waste into a valuable product.